Asymptotically Optimal Successive Overrelaxation Methods for Systems of Linear Equations (Journal of Computational Mathematics, 2021)
We present a class of asymptotically optimal successive overrelaxation methods for solving the large sparse system of linear equations. Numerical computations show that these new methods are more efficient and robust than the classical successive overrelaxation method.
Keywords: Successive Overrelaxation Methods; System of Linear Equations.